Analysis of energy stability in 6/4 MeV dual energy RF electron linac. (1st October 2022) - Rajan, Rehim N.; Mondal, J.; Tillu, A.R.; Sharma, V.; Bhattacharjee, D.; Chandan, Shiv; Yadav, V.; Sharma, Archana
Abstract: RF linear accelerators are used to produce high energy electron beams up to several MeV for various industrial, medical and research applications. Accelerators with switchable energy are increasingly finding application in non-destructive testing systems with material discrimination capability. These systems are based on pulsed accelerators with duration 3 to 10 micro second with repetition rate up to 400 Hz. Magnetrons are used as microwave source in relatively low power accelerator systems. This paper examines various factors affecting the pulse to pulse energy variation in such radiation sources. Contributions from individual subsystems are accounted and the cumulative performance is evaluated. Dose stability improvement with remedial measures has been discussed.